Genetic variability, correlation and path analysis in tamarind (Tamarindus indica L.) - Rajamanickam, C. (Journal of Spices and Aromatic Crops, 2020)
The present study was conducted at the Horticultural College and Research Institute, Periyakulam with the objective to estimate the extent of genotypic and phenotypic coefficient of variation, correlation and path analysis among tamarind genotypes. A remarkable variability was observed among the tamarind collections for all the characters. In all the cases, phenotypic variance was higher than the genotypic variance. Also, phenotypic coefficient of variation was found higher than genotypic coefficient of variation for all the traits. The high heritability coupled with high genetic advance as per cent over mean was observed in the traits such as pod yield plant-1 (98.07%; 76.103%), fruit weight (89.11%; 63.668%), fibre weight (89.95%; 91.967%), shell weight (86.19%; 58.534%) and pulp weight (74.13%; 51.533%) whereas the lowest values were recorded for pod length (34.91%; 13.945%) and tree circumference (20.34%; 8.198%). Thus, it indicated better scope for improvement of these traits through selection programme. Pod yield tree-1 was significantly and positively correlated with pod width, tree circumference and pulp weight. Path coefficient analysis showed that pod yield tree-1 contributed the maximum positive direct effect.